ASUHAN KEPERAWATAN DENGAN MASALAH UTAMA DEMAM TYPHOID - Amalina 'Izazi (Universitas Islam Negeri Alauddin Makassar, 2018)
Typhoid fever is a disease caused by infection with Salmonella typhi bacteria. This disease is still a health problem, especially in developing countries. This disease is closely related to personal hygiene and the surrounding environment such as the use of clean water, management and garbage disposal. Transmission of typhoid fever can be through fecal and oral which enter the human body through contaminated food and drinks. The general purpose of this journal is to describe the management of nursing care with the main problem of typhoid fever. This case study uses descriptive method which describes the process of nursing care by focusing on one of the important problems in the chosen case, namely nursing care with the main problem of typhoid fever.ABSTRAKDemam typhoid adalah penyakit yang disebabkan oleh infeksi bakteri Salmonella typhi. Penyakit ini masih menjadi masalah kesehatan terutama di negara berkembang. Penyakit ini berhubungan erat dengan personal hygiene dan lingkungan di sekitarnya seperti penggunaan air bersih, pengelolaan dan pembuangan sampah. Penularan demam typhoid bisa melalui fecal dan oral yang masuk ke dalam tubuh manusia melalui makanan dan minuman yang terkontaminasi. Tujuan umum dari jurnal ini adalah menggambarkan tentang pengelolaan asuhan keperawatan dengan masalah utama demam typhoid. Study Kasus ini menggunakan metode deskriptif yaitu menggambarkan tentang proses asuhan keperawatan dengan memfokuskan pada salah satu masalah penting dalam kasus yang dipilih yaitu asuhan keperawatan dengan masalah utama demam typhoid.